External and internal psychological resources of support in women with the threat of preterm birth in the third trimester of pregnancy and after the birth - Grinko Наталя (Psychosomatic Medicine and General Practice, 2019)
Introduction. Pregnancy can both change a couple’s relationships for the better and worsen them. The scenario of developing relationships after pregnancy depends mainly on the predominance of constructive and non-constructive motives of conception. Unfortunately, expectant parents are generally unable to grasp these patterns by resorting mainly to rationalization and displacement. The purpose of the study. The purpose of the study was to evaluate the external and internal resources of support for women with the threat of preterm delivery during the third trimester of pregnancy and after childbirth. Materials and methods. The study was conducted during 2011-2019 on the basis of KNP "Storozhinets Regional hospital". The study included 150 pregnant women in the third trimester (23-37 weeks), and their husbands. Of these, the main group consisted of 120 women with the risk of preterm birth in the last trimester of pregnancy (MG). The comparison group consisted of 30 women with physiological pregnancy (CG). The study conducted a clinical interview and psychodiagnostic examination of women using the modified Experiences in Close Relationships-Revised (ECR-R) Adult Attachment questionnaire, Fraley, RC, K. Brennan and R.K. Waller, NG, & Brennan, KA, 2000) and the Multidisciplinary Scale of Perceptions of Social Support (MSPSS) (D.Zimet, 1988). Results and discussion. Thus, it was found that women from MG at all stages of the survey are dominated by disorientation (41-46), somewhat less dependent type (35-36), autonomous (23-29), and much less - avoidance of closeness (14-16), while women from CG are predominantly autonomous type (10-13), less often dependent type (8-10) and avoidance of proximity (4-9), and much less often - disorientation (3-4). The definition of the level of social support showed the following. For MG, the mean of the major scales was as follows: “family support” - µ = 91,667 at standard deviation σ = 2,099; 2) "support for friends" - µ = 89,167 at standard deviation σ = 2,4706; 3) “support for significant others” - µ = 68,125 at standard deviation σ = 3.8; 4) "support of colleagues at work" - µ = 30,833 at standard deviation σ = 3,6324; 5) “NGO support” - µ = 11,458 at standard deviation σ = 2,3464. For GPs, the mean of the baseline scales was higher: “family support” - µ = 94.167 at standard deviation σ = 2.8576; 2) "support for friends" - µ = 91,667 at standard deviation σ = 4,3769; 3) “support for significant others” - µ = 75 at standard deviation σ = 7, 2912; 4) “support of colleagues at work” - µ = 58,333 at standard deviation σ = 7,7063; 5) “NGO support” - µ = 10,833 at standard deviation σ = 4,2689. Significant differences in the distributions of relative frequencies are revealed. At each stage of the survey, there was a decrease in the level of social support in MG compared to CG. Based on the results of a psychodiagnostic study, statistically confirmed results were found regarding higher levels of social support in women with CG. Conclusions. Pregnancy can both change a couple’s relationships for the better and worsen them. The scenario of developing relationships after pregnancy depends mainly on the predominance of constructive and non-constructive motives of conception. The threat of preterm birth is a complex psycho-traumatic situation that, if constellations of the relevant personal characteristics and lack of proper family support can become a trigger for the formation of psychological maladaptation. The development and progression of this phenomenon lead to a worsening of the emotional state of the woman and the child during the first year of life. In this case, the family is not a powerful resource, but a traumatic factor. Studying the external and internal resources of support for women with the threat of premature birth during the third trimester of pregnancy and after childbirth will prevent the negative impact of the threat of premature birth, which will significantly improve the state of psycho-emotional, marital and maternal-child spheres of women.